Microsoft kinect 3D depth data analysis - Liang, Xin (2014)
There is a growing trend of using Kinect depth sensor in various fields such as computer vision, UAV (Unmanned Aerial Vehicle), ground mobile robotic and medical. The main objective of this object is to explore the potential of Kinect as a measuring device. This report investigates the quality of two modes of depth data obtained by the Kinect sensor using Kinect for Windows SDK. Results show that the accuracy of depth measurement decreases with increasing distance to the sensor. The detectable range for normal depth stream is from about 0.8m to 4m and from about 0.5m to 9.7m to the sensor for extended depth stream. Normal depth stream is more accurate than extended depth stream from 0.8m to 4m. This report provides a reference to developers who want to use Kinect as a measuring device to decide whether Kinect is applicable to a specific problem.